Study on water resources and water environment in urban agglomeration - Liu Manli; Wang Ying (E3S Web of Conferences, 2021)
This study is the result of analysis on the influencing factors of water resources and water environment in Beijing-Tianjin-Hebei urban agglomeration during 2010–2019. Based on the spatial and temporal distribution of water resources, the effective utilization rate and recovery rate of water resources, analysis of groundwater exploitation, reservoir construction, surface water pollution, soil erosion, etc., the overall situation of water resources and water environment in the Beijing-Tianjin-Hebei urban agglomeration is obtained, and the water resources are further effectively controlled to strengthen the security of water environment.